2004
DOI: 10.1021/jo0353029
|View full text |Cite
|
Sign up to set email alerts
|

Novel UDP-Glycal Derivatives as Transition State Analogue Inhibitors of UDP-GlcNAc 2-Epimerase

Abstract: The "epimerisation" of UDP-GlcNAc to ManNAc, the first step in the biosynthesis of sialic acids, is catalyzed by UDP-GlcNAc 2-epimerase. In this paper we report the synthesis of transition state based inhibitors of this enzyme. To mimic the assumed first transition state of this reaction (TS 1), we designed and synthesized the novel UDP-exo-glycal derivatives 1-4. We also report herein the synthesis of 5 and 6, the first C-glycosidic derivatives of 2-acetamidoglucal, and the synthesis of the ketosides 7 and 8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 36 publications
2
39
0
1
Order By: Relevance
“…In the light of our new results, it is not surprising that synthetic derivatives of UDP (41,42) have been found to effectively inhibit the enzyme. According to our studies, another apparent requirement for a potent inhibitor is the presence of two or three negative charges.…”
Section: Fig 5 Model For the Design Of Udp-glcnac 2-epimerase Inhibmentioning
confidence: 68%
“…In the light of our new results, it is not surprising that synthetic derivatives of UDP (41,42) have been found to effectively inhibit the enzyme. According to our studies, another apparent requirement for a potent inhibitor is the presence of two or three negative charges.…”
Section: Fig 5 Model For the Design Of Udp-glcnac 2-epimerase Inhibmentioning
confidence: 68%
“…Furthermore, inhibition of sialic acid biosynthesis could render metastatic cells more susceptible to the immune system, because most metastatic cells are protected by a sialic acid shield from immune recognition (47). Because hGNE is the key enzyme in sialic acid biosynthesis and its impairment diminishes the level of sialic acid expression on cell surfaces (14), many UDP-GlcNAc and transition state analogs were synthesized as inhibitors for the epimerase activity of hGNE and tested to date (48,49). However, because of their hydrophilic nature, these inhibitors cannot penetrate the cell plasma membrane and are ineffective in cellular systems.…”
Section: Asp-517-omentioning
confidence: 99%
“…On this basis a mechanism for the epimerisation was postulated. [9,10] We recently reported the design and synthesis of some transition-state-based inhibitors for UDP-GlcNAc 2-epimerase, which showed binding affinities in the range of the natural substrate UDP-GlcNAc. [10] In this study we followed a different approach and turned our interest to mimics of the enzyme substrate, UDP-GlcNAc.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] We recently reported the design and synthesis of some transition-state-based inhibitors for UDP-GlcNAc 2-epimerase, which showed binding affinities in the range of the natural substrate UDP-GlcNAc. [10] In this study we followed a different approach and turned our interest to mimics of the enzyme substrate, UDP-GlcNAc. The results of previous studies [10,11] clearly indicated that the sugar moiety and the UDP residue are both important for binding to the active site of UDP-GlcNAc 2-epimerase.…”
Section: Introductionmentioning
confidence: 99%